Developmental origins, behaviour change and the new public health*. (8th July 2015) - Barker, M.
Abstract : A developmental approach to public health focuses attention on better nourishing girls and young women, especially those of low socio-economic status, to improve mothers' nutrition and thereby the health of future generations. There have been significant advances in the behavioural sciences that may allow us to understand and support dietary change in young women and their children in ways that have not previously been possible. This paper describes some of these advances and aims to show how they inform this new approach to public health. The first of these has been to work out what is effective in supporting behaviour change, which has been achieved by careful and detailed analysis of behaviour change techniques used by practitioners in intervention, and of the effectiveness of these in supporting change. There is also a new understanding of the role that social and physical environments play in shaping our behaviours, and that behaviour is influenced by automatic processes and 'habits' as much as by reflective processes and rational decisions. To be maximally effective, interventions therefore have to address both influences on behaviour. An approach developed in Southampton aims to motivate, support and empower young women to make better food choices, but also to change the culture in which those choices are being made. Empowerment is the basis of the new public health. An empowered public demand for better access to better food can go a long way towards improving maternal, infant and family nutrition, and therefore the health of generations to come.